Sufisme dalam Pandangan Muslim Modernis Awal: Telaah Pemikiran Tasawuf Kiai Moechtar Boechari (1899-1926) - Ali, Mohamad (Jurnal Lektur Keagamaan, 2019)
This research tries to find sufism thought by early modernist muslim from Surakarta, Kiai Moechtar Boechari (1899-1926), by tracing his religious view and Sufism thought. He was a santri and friend of K.H. Ahmad Dahlan (1868-1923) who pioneered in establish Muhammadiyah branch Surakarta. In general, as modernist muslim movement, MuhamÂmadiyah is considered as anti-sufism. In contrast to that, Kiai Boechari paid attention to Sufism by writing a thin book, Tasawoef Tjekakan. This intellectual position is somewhat different from the mainstream modernist Islam movement. To explore this issue, this paper uses historical method by Berkhoferâ€Ÿs situational approach. The result of the research points out, that firstly, religious view of Kiai Boechari is a modernist with authentic formulation, that is: purifying Tauhid, awakening scientific ethos, promoting movement of Islamic modernist, preaching Islam softly, and appreciating womenâ€Ÿs equality. Secondly, the character of Kiai Boechariâ€Ÿs thought on Sufism seems to resemble Imam Al-Ghazaliâ€Ÿs mysticism of personality (transcendental mysticism), only that he modified by reducing zuhud station in order for a sufi to be involved dynamically in many aspects of life.Keywords: Kiai Moechtar Boechari, modernist muslim, sufism, SurakartaÂ Penelitian ini berupaya mengungkap pemikiran tasawuf seorang muslim modernis awal asal Surakarta, Kiai Moechtar Boechari (1899-1926), dengan cara melacak pandangan keagamaan dan corak pemikiran tasawufnya. Dia merupakan santri dan sahabat K.H. Ahmad Dahlan (1868-1923) yang turut mendirikan Muhammadiyah cabang Surakarta. Pada umumnya, sebagai gerakan Islam modernis, Muhammadiyah dipandang anti-tasawuf. Berbeda dengan itu, Kiai Boechari memberi perhatian pada sufisme dengan menulis buku tipis, Tasawoef Tjekakan. Posisi intelektual yang demikian seolah-olah menempatkannya berada â€œdi luar arus utamaâ€ gerakan Islam modernis. Untuk mengeksplorasi masalah tersebut, peneliti memakai metode sejarah dengan pendekatan situasional Berkhofer. Hasil penelitian menunjukkan pertama, pandangan keagamaan Kiai Boechari berhaluan modernis dengan formulasi yang otentik, yakni: memurnikan tauhid; membangkitkan etos keilmuan, aktif di gerakan Islam modern, mendakwahkan Islam dengan kelembutan, dan menghargai kesetaraan perempuan. Kedua, pemikiran tasawuf Kiai Boechari bercorak mistik kepribadian (transendental mistik) seperti halnya Imam Al-Ghazali. Lebih dari itu, dia memodifikasinya dengan tidak memasukkan tangga zuhud, agar sufi lebih dinamis menapaki berbagai aspek kehidupan.Kata kunci: Kiai Moechtar Boechari, muslim modernist, sufisme, Surakarta